An Empirical Study of Islamic Law on the Causes of Immoral Crimes Among Adolescents - Muzakkir; Hidayat, Taufik; Mahera, Najla (State of Islamic Institute Langsa, 2024)
From the perspective of Islamic law, adolescents in the Islamic sharia region (Aceh) should ideally be guided by strong moral and ethical values. Intensive religious education, a harmonious family environment, and a supportive community are the main foundations in the formation of adolescent character. Adolescents who grow up in an environment that emphasizes the importance of prayer, fasting, zakat, and other virtuous values are expected to be able to avoid deviant behavior and criminal acts. However, the situation in Karang Baru, Aceh Tamiang shows a different picture. Many teenagers in this area fall into immoral crimes, both consensual and coercive such as molestation and rape. This article is classified as a literature research with a qualitative approach. The methodology used is normative legal studies and phenomenological studies. The results of the study concluded that the causes of immoral acts are multifactorial and interrelated. Low education and difficult economic conditions are significant factors, exacerbated by an unsupportive environment and easy access to alcohol and unfiltered technology.